Compound parabolic concentrator solar air collection–storage system based on micro-heat pipe arrays. (1st September 2020) - Wang, Ze-yu; Diao, Yan-hua; Zhao, Yao-hua; Wei, Xiang-qian; Chen, Chuan-qi; Wang, Teng-yue; Liang, Lin
Highlights: A novel solar air collector with latent thermal storage system is proposed. The maximum overall efficiency of the proposed solar air system is 17.8%. The connection of heat storage weakens the thermal performance of solar collector. Air volume has a large effect on heat storage efficiency. However, Air volume has a little effect on overall efficiency. Abstract: A novel solar air heating system based on micro-heat pipe arrays was proposed in this work. The system is composed of an evacuated tube solar air heater with a compound parabolic concentrator and a latent heat storage unit. A set of systematic calculation and evaluation methods was proposed according to the heat flow of the solar air system. Heat collection, heat storage, heat release, heat transportation, and the overall processes were considered. Thereafter, the influence of connecting a latent heat storage unit on the heat collection characteristics of the solar air heater was assessed. The thermal response and thermal performance of the system under different air volumes were studied using the proposed evaluation method. Results showed that after the addition of the latent heat storage unit, the average heat collection efficiency of the solar air heater dropped by approximately 10%. The heat collection, storage, release, and extraction power of the system reached 742.2, 611.0, 448.4, and 369.6 W, respectively. The average heat collection, storage, release, and transportation efficiencies reached 29.6%, 93.5%, 98.6%, and 91.0%, respectively. The maximum overall thermal efficiency of the system was 17.7%. Moreover, the results revealed that a large air volume exerts a beneficial effect on heat collection performance but adversely influences the heat storage process.